Vapour–liquid–solid‐assisted growth of cadmium telluride nanowires and their field emission properties. (1st March 2016) - Bagal, Vivekanand S.; Patil, Girish P.; Suryawanshi, Sachin R.; More, Mahendra A.; Chavan, Padmakar G.
Abstract : Cadmium telluride (CdTe) nanowires were grown on silicon substrate (100) by thermal evaporation method. The synthesised CdTe nanowires were characterised by X‐ray diffraction, field emission scanning electron microscope, energy‐dispersive analysis of X‐ray, and photoluminescence techniques. The field emission characteristics have been investigated at room temperature. The J–E and I–t characteristics were measured in a planar diode configuration at the base pressure of 1 × 10 −8 mbar. Turn‐on field defined for the emission current density of 0.1 µA/cm 2 has been found to be 2.2 V/µm and on the application of high applied electric field of 7.8 V/µm maximum current density of 210 µA/cm 2 has been achieved. The I–t measurement has been studied at the preset of 1 µA emission current for the duration of 3 h. Overall nature of emission current has been seen to stable for duration of the measurement. To the best of the authors' knowledge, this is a first report on field emission study of CdTe nanowires.